Время твари: роман : в 2-х томах (Р. В. Злотников) - Злотников Роман Валерьевич (2011)
Экземпляры: ООВ (20160318) / Инвентарный номер: 39092 / Цена: 37.00 / Авт.знак: З-68 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6